Sleep improvement in athletes: use of nutritional supplements - Mata Ordóñez, F.; Sánchez Oliver, A. J.; Carrera Bastos, P.; Sánchez Guillén, L.; Dominguez, R. (Archivos de medicina del deporte, 2017)
Sleep is the physical and mental resting state which is fundamental for recovery of the biological system, regulating key mechanisms and metabolic homeostasis. It is recommended to sleep around 8 hours/night, and sleep restriction is considered when a person sleeps less than 6 hours during 4 or more consecutive nights. Some environmental factors adversely affecting sleep will reduce quality of life and may increase mortality risk. Sports performance is obviously a key factor that needs to be successful in a competition period. It is well known that insufficient rest reduces physical fitness and favors the onset of mood disorders. For that reason, multiple lines of research are focused on finding the best way to improve the quality and quantity of sleep in athletes. It has been found that both nutrition and good training periodization are important to improve the rest and sleep of athletes. To get to sleep and its disruption in the previous days to competition, hour of training, athletes` lifestyle and its impact, nutrition and supplementation, are the key topics addressed in this review about sleep in athletes. There is an urgent need of more research to understand and use different strategies, including nutritional supplements, in improving sleep in athletes.